Transpedal lymphatic embolization for lymphorrhea at the graft harvest site after coronary artery bypass grafting - Cha, Jung Guen (Yeungnam Univ J Med, 2020)
Lymphorrhea is a rare but potentially severe complication that occurs after various surgical procedures. Untreated lymphorrhea may lead to wound dehiscence, infection, and prolonged hospital stay. Currently, there is no standard effective treatment. Early management usually includes leg elevation, drainage, and pressure dressing. However, these methods are associated with prolonged recovery and high recurrence rates. We report a case of lymphorrhea from a calf wound after endoscopic great saphenous vein (GSV) harvesting for coronary artery bypass grafting (CABG). The patient presented with intractable oozing from the postoperative wound on the right calf. Lymphorrhea perGsisted for 6 weeks despite negative-pressure wound therapy with a long-acting somatostatin. We performed unilateral pedal lymphangiography that confirmed wound lymphorrhea, followed by glue embolization. No recurrence was observed after 8 months of follow-up. This case report demonstrates the successful use of lymphangiography with glue embolization in the control of lymphorrhea after GSV harvesting for CABG.